Effects of Micro- and Macroalgae-Supplemented Diets on Growth and Muscle Fibrillar Constitution of Gilthead Seabream, Sparus aurata L., in the Final On-Growing Phase - María Dolores Ayala; Elena Chaves-Pozo; María Isabel Sáez; Francisco Javier Alarcón; Tomás Francisco Martínez; Marta Arizcun (Fishes)
The influence of algae in a final fattening diet for gilthead seabream, Sparus aurata, was studied in an 87 d feeding trial. Five groups were analysed (three tanks per group). In the first 38 days, one lot was fed with standard algae-free feed (C1) and four batches were fed with an algae-free diet low in fishmeal (FM) and fish oil (FO) and rich in terrestrial vegetables (C2). Subsequently, the C2 diet was changed in three out of the four groups, two of them being fed a diet with a microalgae blend (10%) plus 2% macroalgae (Alaria esculenta), either in raw (C2-R) or hydrolysed (C2-H) form, and a third batch with a diet lacking FM and FO but supplemented with 10% microalgae and 7% algae oil (C2-O) for 49 days. Body length and weight, muscle parameters, and conversion index were analysed after 38 and 87 days. At day 38, no significant differences were observed in any parameter between C1 and C2, but at the end of the trial (day 87), C2 displayed the lowest weight gain and the worst conversion rate, whereas C2-R showed higher body weight, fibrillar hypertrophy, and better conversion rates than the other groups, and C2-H displayed higher hyperplasia values than the other groups.